Multiplex PCR-based rapid pathogen identification in acute cholecystitis using the FilmArray BCID2 panel - Nakamura, Gaku; Asai, Koji; Watanabe, Ryutaro; Kuroda, Makoto; Shibahara, Yu; Teraoka, Shintaro; Hagiwara, Osahiko; Kakizaki, Nanako; Sato, Jiro; Watanabe, Manabu; Saida, Yoshihisa (Frontiers in Microbiology, 2025)
PurposeAcute biliary infections are serious conditions in which delayed or inappropriate therapy can worsen clinical outcomes and promote antimicrobial resistance. This study evaluated the FilmArray® Blood Culture Identification 2 (BCID2) panel, a multiplex PCR system, for the rapid detection of pathogens in bile samples from patients with acute cholecystitis.MethodsBile samples were collected intraoperatively or by percutaneous aspiration from 77 consecutive patients with acute cholecystitis. Each specimen was divided for conventional culture and BCID2 panel testing. Culture results served as the reference standard to calculate positive and negative percent agreement (PPA and NPA), predictive values, and accuracy.ResultsBacterial growth was observed in 34 cases (44.2%), yielding 57 isolates from 16 species. The BCID2 panel correctly detected 41 of 46 BCID2-targetable isolates. For detecting at least one pathogen, PPA (sensitivity) was 82.4%, NPA (specificity) 100%, positive predictive value 100%, negative predictive value 91.5%, and overall accuracy 92.2%. Detection was achieved in 70.6% of monomicrobial and 94.1% of polymicrobial infections, with higher bacterial loads (>106 CFU/mL) associated with improved detection rates.ConclusionMultiplex PCR testing using BCID2 panel enables rapid and accurate identification of causative bacteria directly from bile. This approach may support earlier targeted therapy and promote appropriate antimicrobial stewardship in acute biliary infections.